FORMULATION AND EVALUATION OF ZIDOVUDINE LOADED OLIBANUM RESIN MICROCAPSULES: EXPLORING THE USE OF NATURAL RESINS AS BIODEGRADABLE POLYMERIC MATERIALS FOR CONTROLLED RELEASE - Panda, Satyajit (Asian Journal of Pharmaceutical and Clinical Research, 2013)
ABSTRACT The aim of the present study is to develop and evaluate natural biodegradable microcapsules of zidovudine (AZT) by using olibanum resin as microencapsulating agent, which after oral administration could improve the bioavailability of the drug, in order to provide the sustained release to minimize the dose dependent side effects as well as to improve patient compliance. Â An industrially feasible emulsification-solvent evaporation method was used for preparation of different batches of microcapsules. The proposed system was evaluated in vitro for particle morphology, microencapsulation efficiency, production yield, micromeritic properties, release profile and release kinetics etc. Physico-chemical characteristics of AZT and AZT loaded microcapsules were evaluated by differential scanning calorimetry (DSC), X-ray diffraction (XRD), and infrared spectroscopy (FTIR). The resin coated microcapsules were found to be spherical, discrete and free flowing. Microencapsulation efficiency was in a narrow range (81-88%) suggesting an identical distribution of drug in different batches. DSC and XRD results showed a partial modification in AZT's solid state. Zidovudine release from optimized batches of resin coated microcapsules was slow and over 24 hours depending on the core: coat ratio. Drug release was found to be following Fickian diffusion mechanism. The resin coated microcapsules exhibited good controlled release characteristics and were found to be suitable for once a day oral controlled release product. Â 